NILAI TAMBAH DAN BAURAN PEMASARAN PRODUK AGROINDUSTRI JAMUR TIRAM PUTIH PADA RUMAH JAMUR NANDO KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Lia Syafridayanti; Septina Elida (UIR Press, 2024)
White oyster mushrooms have significant potential for enhancement and better negotiating power through agro-industrial initiatives. This study seeks to examine the added value generated from processing white oyster mushrooms into various products, including crispy mushrooms, mushroom nuggets, and mushroom rendang, along with their marketing strategies. The research focuses on the